Tropheryma whipplei-induced plastic bronchitis in children: a case report - Jin, Xuefeng; Zhang, Caiyun; Chen, Chao; Wang, Xiaoning; Dong, Jing; He, Yuanyuan; Zhang, Peng (Frontiers in Pediatrics, 2023)
This article reports a case of a 7-year-old child with severe pneumonia whose chest CT showed pulmonary consolidation and atelectasis, and bronchoscopy revealed plastic bronchitis. The metagenomic Next-Generation Sequencing of the pulmonary lavage fluid suggested that Tropheryma whipplei was the only pathogen. The patient was treated with bronchial lavage to remove sputum plugs, intravenous azithromycin, and piperacillin-tazobactam and was discharged after eight days of hospitalization without any recurrence during follow-up. It is the first case of plastic bronchitis caused by Tropheryma whipplei infection. We aim to increase awareness of Tropheryma whipplei infection among clinical physicians to achieve early diagnosis and treatment. We also hope this report will draw attention to clinical physicians to screen for Tropheryma whipplei in cases of plastic bronchitis of unknown cause.